Endodontics and the ageing patient. (March 2015) - Johnstone, M; Parashos, P
Abstract: Patients are living longer and the rate of edentulism is decreasing. Endodontic treatment is an essential part of maintaining the health and well‐being of the elderly. Retention of natural teeth improves the quality of life and the overall health and longevity of ageing patients. Also, teeth that might be otherwise extracted may be strategically valuable to retain a prosthesis, and elderly patients are more likely to have medical complications that may prevent dental extractions from being safely performed. The technical goals of endodontic treatment in the elderly are the same as those for younger patients. However, the pulpo‐dentinal complex undergoes calcific changes over time, which may pose challenges for the clinician. The purposes of this review are to discuss age changes in the pulp and the challenges posed by diagnosing, treatment planning and treating the elderly endodontic patient.